Self-Realization in Deep Ecology: Is it an Epistemic Virtue? (IUBAT Review, 2026)
This paper explores the concept of self-realization, the basic norm of deep ecology, and argues that it can be understood as an epistemic virtue. In the tradition of the deep ecology movement, self-realization has been portrayed as a lifelong process through which one can expand one's identity and realize a deep connection with all human and non-human entities of nature. However, the moral status of self-realization remains controversial. Existing literature on deep ecology has largely focused on whether self-realization is morally neutral or inherently moral. However, it overlooks the epistemic dimension of self-realization. In order to address this gap, this paper draws insights from virtue epistemology. Using such insights, it conducts a conceptual and critical analysis of the existing literature to determine whether the norm of self-realization can be considered as a character-based epistemic virtue. Through this analysis, this paper argues that self-realization qualifies as an epistemic virtue. In addition, this paper demonstrates that the virtue of self-realization promotes the cultivation of other epistemic virtues and the eradication of ecological ignorance.IUBAT Review—A Multidisciplinary Academic Journal, 8(2): 205-216